2022
DOI: 10.4103/njms.njms_309_21
|View full text |Cite
|
Sign up to set email alerts
|

Minimally traumatic extraction techniques in nonrestorable endodontically treated teeth

Abstract: Aim: The goal of this study was to assess the effectiveness of piezotome as compared to periotome extractions of nonrestorable endodontic treatment of teeth in terms of operational time, pain control, and postoperative bone loss considering the prosthetic rehabilitation in future. Materials and Methods: A double-blind, randomized controlled trial was conducted with 100 patients who wanted single-rooted teeth to be extracted (which failed endodontically)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The piezotome-based atraumatic extraction technique is preferred for immediate implant placement, ensuring minimal damage to the surrounding soft and hard tissues. Research reveals that this technique takes longer than conventional methods, resulting in better tissue preservation and lesser marginal bone loss after implant placement [13][14][15][16]. Using a flapless technique in tooth extraction and implant placement can reduce postoperative tissue loss, shorten operative time, speed up healing, lower the risk of complications, and improve patient comfort [1].…”
Section: Discussionmentioning
confidence: 99%
“…The piezotome-based atraumatic extraction technique is preferred for immediate implant placement, ensuring minimal damage to the surrounding soft and hard tissues. Research reveals that this technique takes longer than conventional methods, resulting in better tissue preservation and lesser marginal bone loss after implant placement [13][14][15][16]. Using a flapless technique in tooth extraction and implant placement can reduce postoperative tissue loss, shorten operative time, speed up healing, lower the risk of complications, and improve patient comfort [1].…”
Section: Discussionmentioning
confidence: 99%
“…This blade is typically used for sharp and precise bone cutting and can be used similarly to the periotome for tooth extraction [ 5 ]. A recent study reported significantly less marginal alveolar bone loss with PSU than with periotome [ 7 ]. In this case, the periodontal ligament was separated to a depth approximately equal to the length of the tip of the flat blade without additional alveolar bone damage using PSU.…”
Section: Discussionmentioning
confidence: 99%